Using group communication to support mobile augmented reality applications - MEIER, RENE; CAHILL, VINNY (IEEE, 2002)
Augmented reality and group communication in wireless ad-hoc networks form relatively new fields of research. When using group communication ordering and timeliness requirements are important. Moreover, when using wireless ad-hoc networks, the possibility of network partition is a serious consideration. In this paper we explore these three issues in the context of using group communication to support mobile augmented reality applications. We describe a policy that enables us to handle partitions and failures, while allowing the members in a partition to make progress, although limited by the application?s consistency requirements. We introduce an approach to determining the message ordering requirements needed to maintain a desired level of consistency and timeliness requirements that should be met in order to have the application state correspond to the sequence of events perceived in the real world.
Proceedings of 5th IEEE International Symposium on Object oriented Real-time Distributed Computing
5th IEEE International Symposium on Object oriented Real-time Distributed Computing
PUBLISHED
(ISORC 2002)
Keywords: Computer Science